Complex Harmonic Motion!

Lets talk about a kind of force, acting on a particle of mass m m , where the mean position is the origin ,is

F = { k x 3 , for x>0 4 k 1 x 5 , for x<0 0 for x=0 \large{ F = \begin{cases} -kx^3 ,\quad \quad \quad \text{for x>0 } \\ -4k_{1}x^5 , \quad \space \space \space \space \text{for x<0}\\ 0 \space \space \space \space \space \space \space \quad \space \space \space \space \space \space \space \space \text{for x=0} \end{cases}} .

Say that the particle is displaced by A A in + v e x +ve \space x direction, and released.

Find the time period.

If your time period comes out to be

T = a b m k 0 A d x A c x c + e m k 1 f g 6 A 2 / 3 0 d x j n A 4 x q T = \large{a \sqrt{\dfrac{bm}{k}} \int_0^A \dfrac{dx}{\sqrt{A^c-x^c}} + \sqrt{\dfrac{em}{k_{1}}} \int_{-\sqrt[6]{\frac{f}{g}} A^{{2}/{3}}}^0 \dfrac{dx}{\sqrt{\frac{j}{n} A^4 -x^q}}}

Find the value of a + b + c + e + f + g + j + n + q a+b+c+e+f+g+j+n+q

Here all of the a , b , c , e , f , g , j , n , q a,b,c,e,f,g,j,n,q are postive integers and gcd ( j , n ) = gcd ( f , g ) = 1 \gcd(j,n)=\gcd(f,g)=1 and e e is square free integer. a a is also square free integer.

Details and Assumptions

  • ( f g 6 × A 2 3 ) \displaystyle{-(\sqrt[6]{\dfrac{f}{g}} \times A^{\tiny \dfrac{2}{3}})} is the lower limit of the second integral

  • Original


The answer is 39.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tapas Mazumdar
Mar 29, 2018

First, consider the positive half of the harmonic oscillation.

We have,

F = k x 3 m a = k x 3 m v d v d x = k x 3 m 0 v v d v = k A x x 3 d x v 2 2 = k 4 m A 4 x 4 ( ) v = k 2 m ( A 4 x 4 ) d x d t = k 2 m ( A 4 x 4 ) 0 t d t = 2 m k 0 A d x A 4 x 4 t = 2 m k 0 A d x A 4 x 4 F = -kx^3 \\ \implies ma = -kx^3 \\ \implies m v \dfrac{dv}{dx} = -kx^3 \\ \implies \displaystyle m \int_0^v v \,dv = -k \int_A^x x^3 \,dx \\ \implies \dfrac{v^2}{2} = \dfrac{k}{4m} \sqrt{A^4 - x^4} \quad {\color{#3D99F6} (*)}\\ \implies v = \sqrt{\dfrac{k}{2m} (A^4 - x^4)} \\ \implies \dfrac{dx}{dt} = \sqrt{\dfrac{k}{2m} (A^4 - x^4)} \\ \implies \displaystyle \int_0^t \,dt = \sqrt{\dfrac{2m}{k}} \int_0^A \dfrac{dx}{\sqrt{A^4-x^4}} \\ \implies \displaystyle t = \sqrt{\dfrac{2m}{k}} \int_0^A \dfrac{dx}{\sqrt{A^4-x^4}}

The value of t t is equal to half time-period of the oscillation on the positive side of the x-axis. The time period for positive half oscillation is thus

T 1 = 2 2 m k 0 A d x A 4 x 4 T_1 = 2 \sqrt{\dfrac{2m}{k}} \int_0^A \dfrac{dx}{\sqrt{A^4-x^4}}

Using ( ) {\color{#3D99F6} (*)} , at x = 0 x=0 , we get v 2 2 = k A 4 4 m \dfrac{v^2}{2} = \dfrac{kA^4}{4m} .


Now, consider the negative half of the harmonic oscillation.

We have,

F = 4 k x 5 m a = 4 k x 5 m v d v d x = 4 k x 5 m v 0 v d v = 4 k x p x 5 d x v 2 2 = 2 k 3 m ( p 6 x 6 ) ( ) v = 4 k 3 m ( p 6 x 6 ) d x d t = 4 k 3 m ( p 6 x 6 ) 0 t d t = 3 m 4 k p 0 d x p 6 x 6 t = 3 m 4 k p 0 d x p 6 x 6 F = -4kx^5 \\ \implies ma = -4kx^5 \\ \implies m v \dfrac{dv}{dx} = -4kx^5 \\ \implies \displaystyle m \int_v^0 v \,dv = -4k \int_x^p x^5 \,dx \\ \implies \dfrac{v^2}{2} = \dfrac{2k}{3m} (p^6 - x^6) \quad {\color{#3D99F6} (**)}\\ \implies v = \sqrt{\dfrac{4k}{3m} (p^6 - x^6)} \\ \implies \dfrac{dx}{dt} = \sqrt{\dfrac{4k}{3m} (p^6 - x^6)} \\ \implies \displaystyle \int_0^t \,dt = \sqrt{\dfrac{3m}{4k}} \int_{-p}^0 \dfrac{dx}{\sqrt{p^6-x^6}} \\ \implies \displaystyle t = \sqrt{\dfrac{3m}{4k}} \int_{-p}^0 \dfrac{dx}{\sqrt{p^6-x^6}}

The value of t t is equal to half time-period of the oscillation on the negative side of the x-axis. The time period for negative half oscillation is thus

T 2 = 2 3 m 4 k p 0 d x p 6 x 6 = 3 m k p 0 d x p 6 x 6 T_2 = 2 \sqrt{\dfrac{3m}{4k}} \int_{-p}^0 \dfrac{dx}{\sqrt{p^6-x^6}} = \sqrt{\dfrac{3m}{k}} \int_{-p}^0 \dfrac{dx}{\sqrt{p^6-x^6}}

Here p p denotes the amplitude of oscillation on the negative side of the x-axis. Using ( ) {\color{#3D99F6} (*)} and ( ) {\color{#3D99F6} (**)} , at x = 0 x=0 , we get

v 2 2 = k A 4 4 m = 2 k 3 m p 6 p = 3 8 6 A 2 / 3 \dfrac{v^2}{2} = \dfrac{kA^4}{4m} = \dfrac{2k}{3m} p^6 \\ \implies p = \sqrt[6]{\dfrac{3}{8}} A^{{2}/{3}}

Hence

T 2 = 3 m k 3 8 6 A 2 / 3 0 d x 3 8 A 4 x 6 T_2 = \sqrt{\dfrac{3m}{k}} \int_{-\sqrt[6]{\frac{3}{8}} A^{{2}/{3}}}^0 \dfrac{dx}{\sqrt{\frac{3}{8} A^4 -x^6}}


The total time period of oscillations is thus

T = T 1 + T 2 = 2 2 m k 0 A d x A 4 x 4 + 3 m k 3 8 6 A 2 / 3 0 d x 3 8 A 4 x 6 T = T_1 + T_2 = 2 \sqrt{\dfrac{2m}{k}} \int_0^A \dfrac{dx}{\sqrt{A^4-x^4}} + \sqrt{\dfrac{3m}{k}} \int_{-\sqrt[6]{\frac{3}{8}} A^{{2}/{3}}}^0 \dfrac{dx}{\sqrt{\frac{3}{8} A^4 -x^6}}

Comparing required values, we get

a + b + c + e + f + g + j + n + q = 2 + 2 + 4 + 3 + 3 + 8 + 3 + 8 + 6 = 39 a+b+c+e+f+g+j+n+q = 2+2+4+3+3+8+3+8+6 = \boxed{39} .

Wow! What a latex you wrote! Let me copy!

Md Zuhair - 3 years, 2 months ago

Log in to reply

Haha. Sure :P

Tapas Mazumdar - 3 years, 2 months ago

Good problem @Md Zuhair

Ankit Kumar Jain - 3 years, 2 months ago

Log in to reply

Thanks Bhai

Md Zuhair - 3 years, 2 months ago

By the way , @Md Zuhair Do you know to delete a set on BRILLIANT?

Ankit Kumar Jain - 3 years, 2 months ago

Log in to reply

No actually, We cant delete a set in brilliant :P

Md Zuhair - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...